Local variations of the stellar velocity ellipsoid – II. The effect of the bar in the inner regions of Auriga galaxies. Issue 3 (23rd March 2022) - Walo-Martín, Daniel; Pinna, Francesca; Grand, Robert J J; Pérez, Isabel; Falcón-Barroso, Jesús; Fragkoudi, Francesca; Martig, Marie
ABSTRACT: Theoretical works have shown that off-plane motions of bars can heat stars in the vertical direction during buckling but is not clear how do they affect the rest of components of the stellar velocity ellipsoid (SVE). We study the 2D spatial distribution of the vertical, σ z, azimuthal, σϕ, and radial, σ r velocity dispersions in the inner regions of Auriga galaxies, a set of high-resolution magneto-hydrodynamical cosmological zoom-in simulations, to unveil the influence of the bar on the stellar kinematics. σ z and σϕ maps exhibit non-axisymmetric features that closely match the bar light distribution with low-σ regions along the bar major axis and high values in the perpendicular direction. On the other hand, σ r velocity dispersion maps present more axisymmetric distributions. We show that isophotal profile differences best capture the impact of the bar on the three SVE components providing strong correlations with bar morphology proxies although there is no relation with individual σ. Time evolution analysis shows that these differences are a consequence of the bar formation and that they tightly coevolve with the strength of the bar. We discuss the presence of different behaviours of σ z and its connection with observations. This work helps us understand the intrinsic σ distribution and motivates the use of isophotal profiles as a mean to quantify the effect of bars.